2009
DOI: 10.1007/s11630-009-0137-y
|View full text |Cite
|
Sign up to set email alerts
|

The simulation and experimental validation on gas-solid two phase flow in the riser of a dense fluidized bed

Abstract: Gas-solid flow in dense CFB (circulating fluidized bed)) riser under the operating condition, superficial gas 15.5 m/s and solid flux 140 kg/m2s using Geldart B particles (sand) was investigated by experiments and CFD (computational fluid dynamics) simulation. The overall and local flow characteristics are determined using the axial pressure profiles and solid concentration profiles. The cold experimental results indicate that the axial solid concentration distribution contains a dilute region towards the up-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…As in our case the value 256 corresponds approximately to loosely packed solids concentration of 57%, the contour values of 60-80 indicate the highest local solids concentration of 13.4%, and occasionally 17.8%, respectively in a very small region just below the exit of the riser, albeit the average solids concentration remains relatively low over the cross section. A recent investigation by Wang et al [23] on a dense fluidized bed reactor also indicated a rather high solids concentration in the upper part of the riser, due to the reflux effect, with even higher values on the wall than the ECT reconstructed values, which shows similar features of a CFB riser as used in this study.…”
Section: Results and Analysissupporting
confidence: 81%
“…As in our case the value 256 corresponds approximately to loosely packed solids concentration of 57%, the contour values of 60-80 indicate the highest local solids concentration of 13.4%, and occasionally 17.8%, respectively in a very small region just below the exit of the riser, albeit the average solids concentration remains relatively low over the cross section. A recent investigation by Wang et al [23] on a dense fluidized bed reactor also indicated a rather high solids concentration in the upper part of the riser, due to the reflux effect, with even higher values on the wall than the ECT reconstructed values, which shows similar features of a CFB riser as used in this study.…”
Section: Results and Analysissupporting
confidence: 81%
“…Circulating fluidized beds (CFB) are applied to a wide area of application, such as powder, combustion, gasification, calcinations and catalytic cracking [1][2][3][4]. With the development of the computer technology, the computational fluid dynamics (CFD) has developed rapidly, which provide low-cost and high efficient design method [5][6][7].…”
Section: Introductionmentioning
confidence: 99%